DNA Methylation and Recurrent Pregnancy Loss: A Mysterious Compass? - Zhou, Qi; Xiong, Yunhe; Qu, Bing; Bao, Anyu; Zhang, Yan (Frontiers in Immunology, 2021)
Recurrent pregnancy loss (RPL) is a common and severe pathological pregnancy, whose pathogenesis is not fully understood. With the development of epigenetics, the study of DNA methylation, provides a new perspective on the pathogenesis and therapy of RPL. The abnormal DNA methylation of imprinted genes, placenta-specific genes, immune-related genes and sperm DNA may, directly or indirectly, affect embryo implantation, growth and development, leading to the occurrence of RPL. In addition, the unique immune tolerogenic microenvironment formed at the maternal-fetal interface has an irreplaceable effect on the maintenance of pregnancy. In view of these, changes in the cellular components of the maternal-fetal immune microenvironment and the regulation of DNA methylation have attracted a lot of research interest. This review summarizes the research progress of DNA methylation involved in the occurrence of RPL and the regulation of the maternal-fetal immune microenvironment. The review provides insights into the personalized diagnosis and treatment of RPL.